2019
DOI: 10.1007/s40262-019-00763-3
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Sampling Strategies for Therapeutic Drug Monitoring of First-Line Tuberculosis Drugs in Patients with Tuberculosis

Abstract: BackgroundThe 24-h area under the concentration–time curve (AUC24)/minimal inhibitory concentration ratio is the best predictive pharmacokinetic/pharmacodynamic (PK/PD) parameter of the efficacy of first-line anti-tuberculosis (TB) drugs. An optimal sampling strategy (OSS) is useful for accurately estimating AUC24; however, OSS has not been developed in the fed state or in the early phase of treatment for first-line anti-TB drugs.MethodsAn OSS for the prediction of AUC24 of isoniazid, rifampicin, ethambutol an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 31 publications
0
22
0
Order By: Relevance
“…According to Magis‐Escurra et al, the model combining C 4 and C 6 was the best to estimate the real AUC ( r = .98) . The combination of C 1 and C 8 gave the best prediction of isoniazid AUC in the study of Saktiawati et al…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…According to Magis‐Escurra et al, the model combining C 4 and C 6 was the best to estimate the real AUC ( r = .98) . The combination of C 1 and C 8 gave the best prediction of isoniazid AUC in the study of Saktiawati et al…”
Section: Discussionmentioning
confidence: 95%
“…However, according to Cojutti et al the best correlation was obtained with C 5 model ( r = .950), while C 3 was poorly correlated with AUC . A recent study by Saktiawati et al performed in Asian population have shown that C 8 was associated with the best correlation as 1‐time‐point model ( r = .956) in fasted conditions . For some authors, isoniazid TDM could be based on a single time point.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, Prahl et al 31 measured the Cmax at 2hours post-dose, but Gengiah et al measured it at 2 1/2 hours post-dose. 22 For accurate prediction of AUC, although recent studies recommending a spare sample of plasma are emerging, 42 intensive blood sampling is essential. But estimation of AUC is also done using different approaches.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several LSSs were proposed for isoniazid alone or in combination with other first-line drugs. Limited sampling strategies were derived from a study with intense sampling of 20 patients conducted in Indonesia, who started on TB medication [ 34 ]. Both studies used the best subset selection, multiple linear regression to calculate LSS and the chosen LSS performed best at estimating the AUC 0–24 h .…”
Section: Anti-tb Drugsmentioning
confidence: 99%